Relative Contribution of Arms and Legs in 30 s Fully Tethered Front Crawl Swimming - Morouço, Pedro (2020)
The relative contribution of arm stroke and leg kicking to maximal fully tethered front crawl swimming performance remains to be solved. Twenty-three national level young swimmers (12 male and 11 female) randomly performed 3 bouts of 30 s fully tethered swimming (using the whole body, only the arm stroke, and only the leg kicking). A load-cell system permitted the continuous measurement of the exerted forces, and swimming velocity was calculated from the time taken to complete a 50 m front crawl swim. As expected, with no restrictions swimmers were able to exert higher forces than that using only their arm stroke or leg kicking. Estimated relative contributions of arm stroke and leg kicking were 70.3% versus 29.7% for males and 66.6% versus 33.4% for females, with 15.6% and 13.1% force deficits, respectively. To obtain higher velocities, male swimmers are highly dependent on the maximum forces they can exert with the arm stroke (r = 0.77, P < 0.01), whereas female swimmers swimming velocity is more related to whole-body mean forces (r = 0.81, P < 0.01). The obtained results point that leg kicking plays an important role over short duration high intensity bouts and that the used methodology may be useful to identify strength and/or coordination flaws.